CAN CLOPIDOGREL FULLY SUBSTITUTE WARFARIN AND DABIGATRAN IN ATRIAL FIBRILLATION? - A. B. Sumarokov (Кардиоваскулярная терапия и профилактика)
Commentary on the paper “Age and effectiveness and safety of various antithrombotic therapy variants in patients with nonvalvular atrial fibrillation” by Shevelev V. I. and Kanorskyi S. G. (Cardiovascular Therapy and Prevention 2013;12 (1):46–53).